Imaging Internal Defects with Synthetic and Experimental Data - Hongwei Zhou; Guanghui Hu; Ling Ma (International Journal of Antennas and Propagation)
This work concerns an inverse time-dependent electromagnetic scattering problem of imaging internal defects in a homogeneous isotropic medium. The position and cross section of the defects are detected by transient electromagnetic pulses in the case of TE polarization. We apply the Kirchhoff migration scheme to locate the position of small objects from both synthetic and experimental data. The multiple-input-multiple-out scheme is used to recover extended scatterers from the data generated by the software GprMax. Numerical experiments show that the Kirchhoff migration method is not only efficient but also robust with respect to polluted data at high noise levels. Experimental results show good quantitative agreement with numerical simulations.